Courtyard as a passive cooling design strategy in Malaysian linked houses / Mohd Riza Ismail - Ismail, Mohd Riza (Institute of Graduate Studies, UiTM, 2017)
Sixty percent of Malaysians prefer to stay in linked houses for reasons of location, space and aesthetic. Most of these houses are installed with mechanical cooling and air circulating fans for thermal comfort instead of a more passive means. There are less demand for courtyard linked houses although the courtyard could hypothetically to be the answer for a passive cooling design strategy. Hence, the aim of this research is to explore the possibilities of enhancing indoor thermal comfort condition by determining the effectiveness of courtyard as a passive cooling building element. The objectives of this thesis are: i) to study the types of courtyard configuration in existing linked houses; ii) to investigate the environmental condition of the courtyard and its effect to the indoor thermal comfort; iii) to explore the importance of courtyard configuration in providing good natural ventilation and iv) to determine the best courtyard configuration that create best indoor thermal comfort of a linked house. This study investigated two similar urban linked houses (with and without internal courtyard) in terms of size and specifications in Shah Alam and Klang…